2006
DOI: 10.1111/j.1440-1746.2006.04674.x
|View full text |Cite
|
Sign up to set email alerts
|

Management consensus of inflammatory bowel disease for the Asia–Pacific region

Abstract: At the present there are no large-scale epidemiologic data on inflammatory bowel disease (IBD) in the Asia-Pacific region, but several studies have shown an increased incidence and prevalence of IBD in this region. Compared to the West, there appears to exist a time lag phenomenon. With regard to the two main forms of IBD, ulcerative colitis (UC) is more prevalent than Crohn's disease (CD). In addition to geographic differences, ethnic differences have been observed in the multiracial Asian countries. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
192
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(198 citation statements)
references
References 56 publications
5
192
0
1
Order By: Relevance
“…It reflects the clinical representation of UC and is the most extensive and simplest DAI. It is adopted by the guidelines for the management of infl ammatory bowel disease in the fourth Asia Pacific Digestive Week [28] . Our results showed that fecal calprotectin concentrations were signifi cantly higher in the patients with active UC than in the patients with inactive UC and in the controls.…”
Section: Discussionmentioning
confidence: 99%
“…It reflects the clinical representation of UC and is the most extensive and simplest DAI. It is adopted by the guidelines for the management of infl ammatory bowel disease in the fourth Asia Pacific Digestive Week [28] . Our results showed that fecal calprotectin concentrations were signifi cantly higher in the patients with active UC than in the patients with inactive UC and in the controls.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of the UC patients came from the Westeast Lake District and Nanchang County of Nanchang City, and Yicheng County of Yicheng City. The diagnosis of UC had been established by clinical, endoscopic, histological, and/ or radiological criteria [16]. Endoscopy was performed in most of the patients and revealed typical signs of UC.…”
Section: Methodsmentioning
confidence: 99%
“…The incidence and prevalence of human bowel diseases such as IBD have shown a dramatic increase in the last decades (11,12). Although the exact cause of IBD is unknown, studies have provided evidence that a dysregulated immune response, genetic factors, enteric flora, and environmental factors contribute to the pathogenesis of IBD (13)(14)(15)(16).…”
mentioning
confidence: 99%